2005
DOI: 10.1128/aem.71.4.2175-2178.2005
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity of Staphylococcus aureus Biofilms in Response to Fluid Shear Allows Resistance to Detachment and Facilitates Rolling Migration

Abstract: Staphylococcus aureus is a leading cause of catheter-related bloodstream infections and endocarditis. Both involve (i) biofilm formation, (ii) exposure to fluid shear, and (iii) high rates of dissemination. We found that viscoelasticity allowed S. aureus biofilms to resist detachment due to increased fluid shear by deformation, while remaining attached to a surface. Further, we report that S. aureus microcolonies moved downstream by rolling along the lumen walls of a glass flow cell, driven by the flow of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
143
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 19 publications
6
143
3
Order By: Relevance
“…In fact, modern biofilms and microbial mats are found to behave like viscoelastic films (Shaw et al, 2004;Vinogradov et al, 2004;Rupp et al, 2005;Lieleg et al, 2011). Lieleg et al (2011) have shown that biofilms display elastic-like responses for high frequency stimuli, and viscous-fluid responses when low frequency mechanical stimuli are applied.…”
Section: Physical Properties Of Microbial Matsmentioning
confidence: 99%
“…In fact, modern biofilms and microbial mats are found to behave like viscoelastic films (Shaw et al, 2004;Vinogradov et al, 2004;Rupp et al, 2005;Lieleg et al, 2011). Lieleg et al (2011) have shown that biofilms display elastic-like responses for high frequency stimuli, and viscous-fluid responses when low frequency mechanical stimuli are applied.…”
Section: Physical Properties Of Microbial Matsmentioning
confidence: 99%
“…Particular focus has been given to the viscoelasticity of cell attachment and detachment, under the influence of antibiotics and flows with different shear rates [14][15][16]. In these studies, the analysis of cells detachment was performed only in small time slots, at specific biofilm growth stages.…”
Section: Introductionmentioning
confidence: 99%
“…1, the relationship between the deformation and growth of immersed biofilms and the shear stresses generated by the surrounding fluid flow is complex and bidirectional. Biofilm morphology influences local flow patterns and hence the fluxes of dispersed phases such as nutrients, metabolites, and quorum sensing molecules [86,87,101], and flow can drive biofilm morphogenesis to rippled beds [42,89], streamers [80,89,90,101], and rolling clusters [79]. The relevance of such process to the formation, growth, and dispersal of both infectious and non-infectious biofilms demands quantitative modelling with a predictive capability, but this situation is far from being realised.…”
Section: Fluid-structure Couplingmentioning
confidence: 99%